In-Silico analysis of binding site features and substrate selectivity in plant flavonoid-3-o glycosyltransferases (F3GT) through molecular modeling, docking and dynamics simulation studies - Sharma, Ranu; Panigrahi, Priyabrata; Suresh, C. G. (Plos One, 2014)
Flavonoids are a class of plant secondary metabolites that act as storage molecules, chemical messengers, as well as participate in homeostasis and defense processes. They possess pharmaceutical properties important for cancer treatment such as antioxidant and anti-tumor activities. The drug-related properties of flavonoids can be improved by glycosylation. The enzymes glycosyltransferases (GTs) glycosylate acceptor molecules in a regiospecific manner with the help of nucleotide sugar donor molecules. Several plant GTs have been characterized and their amino acid sequences determined. However, three-dimensional structures of only a few are reported. Here, phylogenetic analysis using amino acid sequences have identified a group of GTs with the same regiospecific activity. The structures of these closely related GTs were modeled using homologous GT structures. Their substrate binding sites were elaborated by docking flavonoid acceptor and UDP-sugar donor molecules in the modeled structures. Eight regions near the acceptor binding site in the N- and C-terminal domain of GTs have been identified that bind and specifically glycosylate the 3-OH group of acceptor flavonoids. Similarly, a conserved motif in the C-terminal domain is known to bind a sugar donor substrate. In certain GTs, the substitution of a specific glutamine by histidine in this domain changes the preference of sugar from glucose to galactose as a result of changed pattern of interactions. The molecular modeling, docking, and molecular dynamics simulation studies have revealed the chemical and topological features of the binding site and thus provided insights into the basis of acceptor and donor recognition by GTs.